ACARICIDAS NO CONTROLE DO ÃCARO DO BRONZEAMENTO â€“ ð˜ˆð˜¤ð˜¶ð˜ð˜°ð˜±ð˜´ ð˜ð˜ºð˜¤ð˜°ð˜±ð˜¦ð˜³ð˜´ð˜ªð˜¤ð˜ª (MASEE, 1937) NA CULTURA DO TOMATEIRO - Ramalho, F. S.; Veiga, A. F. de S. LeÃ£o (REVISTA DE AGRICULTURA, 2020)
ACARICIDAS NO CONTROLE DO ÃCARO DO BRONZEAMENTO â€“ ð˜ˆð˜¤ð˜¶ð˜ð˜°ð˜±ð˜´ ð˜ð˜ºð˜¤ð˜°ð˜±ð˜¦ð˜³ð˜´ð˜ªð˜¤ð˜ª (MASEE, 1937) NA CULTURA DO TOMATEIRO